Oral Health of 7- to 9-Year-Old Children Born Prematurely—A Case–Control Observational Study with Randomized Case Selection - Heide L. Schlesinger; Roswitha Heinrich-Weltzien; Ina M. Schüler (Dentistry Journal)
Background: Along with the long-term sequelae of preterm birth for general health, oral health is potentially influenced by prematurity due to developmental and behavioral peculiarities. Objectives: This study aimed to compare oral health parameters in the mixed dentition of prematurely and full-term born children. Methods: Dental caries, developmental defects of enamel (DDE), and gingival inflammation were assessed in 7-to-9-year-old children (n = 38) born preterm (PT) compared to a matched control group born full-term (FT) in Germany. Dental caries was recorded using the International Caries Detection and Assessment System (ICDAS II) and DMFT/dmft-criteria. DDE was scored with modified DDE-Index and periodontal health by Periodontal Screening Index (PSI). Statistical analysis included McNemar’s test and Poisson regression. The significance level was p ≤ 0.05. Results: Caries prevalence was 47.4% in PT and 57.9% in FT. In the primary dentition, FT children were significantly more affected than PT children (1.6 dmft vs. 2.7 dmft; p = 0.035). PT children with extremely low birthweight (ELBW) had the highest caries experience (3.2 dmft; 1.0 DMFT). Prevalence of DDE in primary teeth was significantly higher in PT (55.3%) than in FT children (28.9%; p = 0.008). PSI was 3.8 in PT and 3.3 in FT children, but significantly higher in PT children with ELBW (7.4; p = 0.125). Conclusions: PT children are at higher risk for DDE in primary teeth and compromised periodontal health than FT children. Children with ELBW are most susceptible for dental caries and gingivitis.